An ex-ante evaluation of the French car feebate. (February 2023) - Kessler, Louise; Morvillier, Florian; Perrier, Quentin; Rucheton, Keyvan
Abstract: France has a National Low-Carbon Strategy (NLCS), which outlines expected emissions reductions in each sector, and for new vehicles in particular. However, despite the introduction of a feebate on cars in 2008, emissions of new cars have repeatedly exceeded government targets. This highlights the need for tools to estimate ex ante the impact of the feebate on new vehicle emissions. In this paper, we develop an econometric model to estimate the impact of the government's planned feebate on vehicle sales, based on a new dataset of vehicle sales from 2014 to 2019. According to our results, the government's feebate rate currently projected until 2025 is not compatible with the emission reduction targets set in the national strategy. The government's rate would only reduce emissions by 14.1% by 2025, while the emissions reduction calculated from the NLCS data is around 28% over the period. A major overhaul of the scale would therefore be necessary to achieve the climate objectives of the French roadmap. In this paper we present two alternative scale proposals for the period 2022–2025, which would lead to a reduction in greenhouse gas emissions from new vehicles, in line with NLCS based reduction estimates. Highlights: We built an econometric model of car sales to estimate the impact of public policies. We use a novel dataset with sales from 2014 to 2019 including EV and hybrid cars. The planned feebate rates are not aligned with the French national climate strategy. Aligning the feebate implies a significant tightening of the current rates. Complementary measures will be useful to secure the climate objectives.